Line of sight how improved information, transparency, and accountability would promote the adequate resourcing of health facilities across Papua New Guinea. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
It explores information gaps and transparency issues that undermine health service delivery and outcomes. Recommendations in this report aim to improve health sector governance and capacity, which will ultimately contribute to a more robust and equitable health care system.
Keywords: Health care reform -- Southwestern Pacific; Health care reform -- Research -- Asia; Electronic book